Islamic Education and Pluralism: An Overview of Multicultural Education Management - Rahmat Fauzi; Khairil Anwar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Background: Pluralism and multiculturalism are critical issues in the context of global education, particularly in increasingly diverse societies in terms of culture, religion, and ethnicity. Islamic education, as a value-based spiritual education system, holds significant potential in shaping inclusive and tolerant communities. However, challenges arise when exclusive interpretations of religious teachings hinder the development of a pluralistic educational approach. Aim: This study aims to examine the relationship between Islamic education and multicultural education management in efforts to develop an education system that is responsive to diversity. Method: The research employed a literature study approach by reviewing 50 scientific articles, from which 15 were selected based on their relevance to the theme, methodological approach, and contribution to the discourse. The selection process was carried out in three stages to identify articles that specifically addressed the values of pluralism, strategies of education management, and the challenges of implementation in the context of Islamic education. Results: The analysis revealed that pluralism, from the perspective of Islam, is an authentic value reflected in the teachings of the Qur’an, which emphasizes the importance of mutual understanding and respect for differences. Islamic education was found to be highly relevant to multicultural education management, as both prioritize justice, equality, and tolerance. Strategies identified include the integration of multicultural content into the curriculum, teacher training, inclusive classroom management, and anti-discrimination policies. Discussion: The study highlights key challenges, including limited teacher understanding of multicultural concepts, societal resistance to pluralism, and underdeveloped educational policies supporting diversity. To address these challenges, solutions such as curriculum reform, capacity-building for educators, and the creation of safe and inclusive learning environments are proposed. These strategies aim to strengthen the capacity of Islamic educational institutions to manage diversity effectively. Conclusion: This study concludes that Islamic education can serve as a strategic force in developing a multicultural education system. It contributes significantly to the creation of a peaceful, just, and respectful society by embedding the values of pluralism within educational management practices.